Analysis Competitiveness Indonesian Nutmeg Commodities in Global Market - Ernah, Ernah; Alawi, Muhammad Ridwan; Fadillah, Futri Fauza; Souw, Antonius (Jurnal Dinamika Sosial Ekonomi, 2024)
Nutmeg has high economic value and is an important trade commodity for Indonesia. However, the decline in nutmeg exports shows that there are problems that must be resolved in order to remain competitive in the global market. To assess the comparative competitiveness of Indonesian nuts in export destination markets, namely China, Vietnam, India, the Netherlands, and the United States, this study uses the Revealed Comparative Advantage (RCA) method and secondary data, namely time series data for 10 years from 2013 to 2022, with a statistical descriptive approach. Based on this data, it can be concluded that Indonesian nutmeg is competitively in the global market, as evidenced by the RCA value of more than one in five export destination countries. India has the lowest RCA value, while the Netherlands is the main market with the highest value. For future development, the Indonesian government should prioritize the development of markets such as China, Vietnam, and India, and stakeholders should work together more closely to increase the competitiveness of Indonesian nutmeg commodities in the international market.